On the Emergence of Candida auris: Climate Change, Azoles, Swamps, and Birds - Arturo Casadevall (American Society for Microbiology, 2019)
ABSTRACT The most enigmatic aspect of the rise of Candida auris as a human pathogen is that it emerged simultaneously on three continents, with each clade being genetically distinct. Although new pathogenic fungal species are described regularly, these are mostly species associated with single cases in individuals who are immunosuppressed. In this study, we used phylogenetic analysis to compare the temperature susceptibility of C. auris with those of its close relatives and to use these results to argue that it may be the first example of a new fungal disease emerging from climate change, with the caveat that many other factors may have contributed.